The doctrine of professor I. S. Tishkevich and its influence on the grounds for punishment of an unfinished crime - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2019)
The article studies the aspects of formation in the Belarusian legislation of the grounds of punishment of an unfinished crime paying attention to the scientific ideas of professor I. S. Tishkevich. It analyzes the characteristics of the implementation of the theoretical developments of the famous Soviet and Belarusian scientist in the norms of criminal liability (grounds and conditions, system of penalties, order of application) of the Criminal code of the Republic of Belarus (1999) from the perspective of the accumulated experience of the national judicial practice in criminal cases and the transformations that have occurred in the criminal law policy of Belarus. Modern approaches to differentiation of limits of punishment for preparation for a crime and attempt at a crime are being discussed and substantiated by that article. It also develops the theory of differentiation of the limits of punishment of an unfinished crime. It is concluded that it is necessary to add in the criminal law the rules of final punishment by absorbing a less severe punishment more severe in cases where the set of crimes includes at least one serious or particularly serious unfinished crime, significantly distinctive from the other unfinished crimes forming a set in the degree of public danger. It is proposed to establish in the law the restriction of the maximum limits of the final punishment for a set of unfinished crimes provided in the Criminal code of the Republic of Belarus, in determining it by partial or complete addition.